Self-Organized Micro-Columns and Nano-Spheres Generated by Pulsed Laser Ablation of Ti/A1 Alloy in Water - 崔清强 刘向东 陈明 赵明文 王春省 李爽 (中国物理快报：英文版, 2014)
Dense arrays of micro-columns are formed on the surface of Ti-AI alloy by cumulative nanosecond pulsed laser ablation in water. The fabric-like structure characterized by Ti-A1 nano-spheres absorbed on micro-duster in liquid is most likely responsible for the occurrence of laser micro-etching and localized melting, resulting in continuous deepening of micro-holes and the formation of micro-columns. Laser induced plasma spectroscopy is carried out to reveal the effect of micro-columns on subsequent pulse laser ablation. The intensity of spectral lines from Ti ions by additional laser ablation of the modified spot is higher than that created over a smooth surface. These results suggest that the micro-columns lead to an enhanced absorption of the following laser energy. The proposed results and relevant discussions are of importance for the development of light-trapping coatings on a metal surface.